2022
DOI: 10.3390/ijms23137139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ferroptosis on Male Reproduction

Abstract: Ferroptosis is a relatively novel form of regulated cell death that was discovered in 2012. With the increasing research related to the mechanisms of ferroptosis, previous studies have demonstrated that the inactive of the intracellular antioxidant system and iron overload can result in the accumulation of reactive oxygen species (ROS), which can ultimately cause lipid peroxidation in the various cell types of the body. ROS accumulation can cause sperm damage by attacking the plasma membrane and damaging DNA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 90 publications
(99 reference statements)
1
10
0
Order By: Relevance
“…The same type of outcome was observed in the context of arsenite-induced male reproductive toxicity, where testicular cell death was shown to depend on the mechanism of ferroptosis. Several male reproductive diseases are known to depend on the ferroptosis mechanism due to the deposition of iron or ROS in testis as well as the dependency of spermatogenesis on iron abundance [ 143 ]. In this case however, 6-month exposure to drinking water contaminated with arsenite as low as 5 mg/L was shown to underlie pathological changes in mouse testis (2.5 μM in the case of GC-2spd cells cultured in vitro).…”
Section: Poisons and Toxicantsmentioning
confidence: 99%
“…The same type of outcome was observed in the context of arsenite-induced male reproductive toxicity, where testicular cell death was shown to depend on the mechanism of ferroptosis. Several male reproductive diseases are known to depend on the ferroptosis mechanism due to the deposition of iron or ROS in testis as well as the dependency of spermatogenesis on iron abundance [ 143 ]. In this case however, 6-month exposure to drinking water contaminated with arsenite as low as 5 mg/L was shown to underlie pathological changes in mouse testis (2.5 μM in the case of GC-2spd cells cultured in vitro).…”
Section: Poisons and Toxicantsmentioning
confidence: 99%
“…Free PUFAs can be ultimately converted to phosphatidylethanolamine (PE)-PUFAs-OOH by three important enzymes, ACSL4, lysophosphatidylcholine acyltransferase 3 (LPCAT3), and lipoxygenases (LOXs; Jiang et al, 2020 ). The formation of lipid peroxides involves the formation of AA-PE from phosphatidylethanolamine (PE), an essential component of cell membranes, and arachidonic acid (AA), a PUFA, catalyzed by ACSL4 and LPCAT3, which is then peroxidized by iron-dependent LOX to form AA- OH -PE, the major actuator of ferroptosis ( Protchenko et al, 2021 ; Liu et al, 2022 ), this is shown in Figure 4 . ACSL family made up of proteins on the endoplasmic reticulum and outer membrane, ACSLs are responsible for the formation of fatty acid acyl coenzyme a esters from free long-chain fatty acids.…”
Section: Excess Glutamate Accumulation Can Inhibit the Cystine/glutam...mentioning
confidence: 99%
“…27 Acute ferroptosis can result in oxidative stress in the testes and oxidative damage to sperm DNA, ultimately leading to testicular disorders. 28 Previous studies have reported that DEHP can lead to lipid metabolism alterations 29 and ferroptosis in testes. 30,31 In this study, we performed lipidomics analysis and detected indicators related to the ferroptosis pathway in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid metabolism is essential for testicular development, and alterations in lipid metabolism are closely associated with testicular atrophy 27 . Acute ferroptosis can result in oxidative stress in the testes and oxidative damage to sperm DNA, ultimately leading to testicular disorders 28 . Previous studies have reported that DEHP can lead to lipid metabolism alterations 29 and ferroptosis in testes 30,31 …”
Section: Introductionmentioning
confidence: 99%